Oxide Gabbros: Transformation From Oceanic Ridge‐Transform Systems to Subduction - Thomas Gyomlai; Cécile Prigent; Sampriti Mukherjee; Alexandre Janin; Mathilde Cannat; Saskia Erdmann (Geochemistry, Geophysics, Geosystems)
Abstract Fluid composition and fluxes in subduction zones are primarily governed by the nature and degree of hydrothermal alteration of the subducting oceanic lithosphere. However, spatial and temporal heterogeneities inherited from mid‐ocean ridge and oceanic transform fault (OTF) systems introduce significant uncertainties in constraining these fluid variations. Here, we focus on the effect of subducting Fe‐Ti‐rich gabbroic rocks (oxide gabbros), which are commonly found in (ultra)slow‐spread oceanic crust along OTF walls, in detachment faults forming at the inside corners of ridge‐transform intersections (RTIs) and within subducted oceanic metamorphic units. We carried out a petrological and geochemical characterization of oxide gabbros from the Vema OTF which segments the mid‐Atlantic Ridge to document and discuss their abundance, composition, formation and transformation processes at RTIs. Results illustrate spatially variable magmatic and hydrothermal processes at RTIs, resulting in variable Fe‐Ti‐(P)‐(H2O)‐V enrichment (ilmenite + titanomagnetite ± apatite ± amphibole ± olivine) of primary gabbroic rocks. Thermodynamic modeling reveals significant variability in the stability of hydrated phases across different gabbroic compositions, indicating that, in subduction zones, Fe‐Ti‐enriched lithologies release fluids at shallower depths. Oxide gabbros, like the ones studied, represent a significant but often overlooked source of H2O, halogens and large ion lithophile elements to the mantle wedge. In addition, subducted P‐rich oxide gabbros may serve as a deep (>700 km) source of fluorine in the asthenosphere. Our results demonstrate that subduction of a compositionally heterogeneous slab containing significant amounts of oxide gabbros generates a broad dehydration domain with implications for seismicity, water transport along the subduction interface and fluid‐mediated tectonic slicing.